Surgical site infection after orthognathic surgery caused by uncontrolled periodontitis: A case report - Jiahong Shi; Diya Xie; Lang Lei; Hou-xuan Li (Elsevier, 2022)
A 34-year-old man suffered from continuous suppuration at the mandibular second molar after orthodontic-orthognathic surgery. Several systemic anti-inflammatory and local antibiotic treatments were prescribed to arrest the infection, and the titanium plate at the right mandible was removed to avoid its contamination. However, such treatment modalities failed to control the infection, and the suppuration persisted. Periodontitis is a risk factor for infection after orthognathic surgery. Periodontal status should be thoroughly established in patients who need orthognathic surgery.